The Relationship Between Library Principal Leadership Style and Teacher Work Motivation in Private Schools - Firayani, Firayani (PT. Anagata Sembagi Education, 2025)
Abstract This study aims to examine the relationship between principal leadership style and teacher work motivation in private schools through a literature review approach. In the context of private education, the principal's leadership style is a crucial factor in creating a supportive, collaborative, and motivating work environment. Analysis of various scientific articles indicates that transformational, democratic, and instructional leadership styles are most effective in improving teacher motivation and performance. Teachers who feel involved in decision-making and receive personal support from their leaders tend to have high intrinsic motivation, which impacts teaching quality and positive relationships with students. On the other hand, authoritarian and laissez-faire leadership styles are considered less effective and can even reduce teacher morale. The context of private schools, which often face limited resources, requires principals to be adaptive and responsive to teacher needs. This study confirms that effective leadership not only improves teacher performance but also creates a more positive and productive learning environment for students. These findings provide an important contribution to formulating leadership development policies in private education settings